A comparative study between wide local excision with lay open versus Limberg flap transposition in the management of pilonidal sinus disease – A single center study - Om Prakash Palsania; Galwa, Rajneesh; Garima Choudhary; Singh, Narender; Meena, Sunil Kumar (Asian Journal of Medical Sciences, 2023)
Background: Pilonidal sinus disease (PSD) is a tract in the sacrococcygeal region’s subcutaneous tissue that presents with recurrent infection and persistent inflammation. The best surgical strategy for treating pilonidal sinus illness is still up for debate, despite the fact that several surgical techniques for treating the sacrococcygeal pilonidal sinus have been identified. Aims and Objectives: This study evaluated several intraoperative and post-operative constraints related to the surgical techniques of wide excision with lay open and Limberg flap transposition for treating pilonidal sinus. Materials and Methods: The division of 50 symptomatic pilonidal sinus patients into two equal groups was based on simple randomization. Patients in Group-A had wide local excisions with lay open, whereas those in Group-B received wide excisions with Limberg flaps. Operative time along with post-operative issues including pain, seroma, infection, necrosis of the flap’s tip, gaping, loss of sensation, and recurrence was compared between the two groups. Results: When compared to the wide excision group, the mean operating time was substantially greater in the Limberg flap repair group. There was a significant difference between the groups in terms of the average number of days spent in the hospital (Group-B was 6.8±1.5 days and Group-A was 12.96±1.3 days), the average number of days it took for the wound to heal (Group B was 16.6±8.5 days and Group-A was 49.5±7.8 days), mean work-off periods (Limberg’s rhomboid flap - 19.64±5.1 days and laying open technique - 52.6±8 days), and mean number of days pain lasted (Group-B - 14.8±5.7 days and Group-A - 45.6±7.5 days). Wide local excisions are associated with increased wound infection. Recurrence in Limberg’s rhomboid flap group was less (4% vs. 16% with laying open approach). Conclusions: Low recurrence rates and comparably few complications are associated with rhomboid excision with Limberg flap repair transposition surgery. The primary course of action for pilonidal sinus illness should be Limberg flap repair.